Advanced AutoCAD 2015 exercise Workbook - Shrock, Cheryl R.; Heather, Steve (Industrial Press Inc., 2014)
Advanced AutoCAD® 2015 Exercise Workbook is the right book for users if they liked the author's Beginning AutoCAD® Exercise Workbook, or they're looking for a clear, no nonsense, easy-to-follow text, or they want to learn more about AutoCAD® such as Xref, Attributes, and 3D solids. Totally updated for AutoCAD 2015 and 2015 LT, it offers several new and improved features.